Using Anime as A Teaching Media to Improve Understanding of Sentence Patterns in Japanese - Nining Sukaesih; Retno Utari (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study aims to examine the effectiveness of anime as a learning medium in improving students’ understanding of Japanese sentence patterns, specifically tai desu, temo ii desu, and nakereba narimasen, among Tokutei Ginou program students at LPK SBN Tangerang. The research employed a quantitative approach using a quasi-experimental one-group pretest–posttest design. The participants consisted of beginner-level Japanese learners (JLPT N4–N5) selected through purposive sampling. Data were collected through pre-tests and post-tests to measure students’ comprehension of sentence patterns, as well as questionnaires to identify students’ perceptions of anime-based learning. The treatment was conducted through anime-based instruction using The Secret World of Arrietty as learning media. Data analysis included normality tests, homogeneity tests, paired-sample t-tests, and regression analysis. The results showed a significant improvement in students’ understanding of Japanese sentence patterns after the use of anime media, with significance values below 0.05. Regression analysis also indicated that anime media had a positive and significant effect on learning outcomes. Furthermore, questionnaire results revealed that students had very positive responses toward the use of anime, considering it engaging, contextual, and easy to understand. Therefore, it can be concluded that anime is an effective and appropriate learning medium for improving Japanese sentence pattern comprehension among LPK SBN students